2016
DOI: 10.1016/j.ajog.2016.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and uterine fibroid risk in hyperlipidemia patients: a nested case-control study

Abstract: Background Statins are 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase inhibitors primarily used for treatment of hyperlipidemia. Recently, they have been shown to inhibit proliferation of uterine fibroid cells and inhibit tumor growth in fibroid animal models. Objectives To examine the association between statin use and the risk of uterine fibroids and fibroid-related symptoms in a nationally representative sample of commercially insured women diagnosed with hyperlipidemia. Study Design We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 51 publications
1
24
2
1
Order By: Relevance
“…Hyperlipidaemia is a widespread disease and a major risk factor for many other diseases. Although lots of chemical drugs, including statins and fibrates, used for the treatment of hyperlipidaemia, most of the drugs are usually expensive and lead to some negative effects, such as cognitive disorder, diabetes mellitus and uterine fibroids [15,16]. Moxibustion and acupuncture had been considered as potential treatments for hyperlipidaemia [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidaemia is a widespread disease and a major risk factor for many other diseases. Although lots of chemical drugs, including statins and fibrates, used for the treatment of hyperlipidaemia, most of the drugs are usually expensive and lead to some negative effects, such as cognitive disorder, diabetes mellitus and uterine fibroids [15,16]. Moxibustion and acupuncture had been considered as potential treatments for hyperlipidaemia [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…43 In a large nested case-control study including over 190,000 patients, the same group compared statin use in women with fibroids (cases) and those without fibroids (controls). 44 They found that exposure to statins in the previous 2 years was associated with a decreased risk of fibroids, with an odds ratio of 0.85. Additionally, women who took statins were less likely to have menorrhagia, anemia, pelvic pain, or undergo myomectomy.…”
Section: Simvastatinmentioning
confidence: 99%
“…Borahay who had been studying fibroid development and effects of simvastatin showed that simvastatin acted by reducing mitogen activated protein kinase (MAPK) and protein kinase B signaling pathway phosphorylation along with inducing Calcium dependent apoptosis of uterine fibroid cells both in vivo and in vitro along with increasing caspase -3 activity, particularly at micromolar levels of 0.1-10µM. 8,9 To examine further the anti-uterine fibroid effects of treatment with simvastatin in vivo using immuno deficient mice xenografted with human uterine fibroid tissue ,They supplemented mice with E2/P pellets to mimic the hormone effects on Uterine fibroids 8,9 initially. This was followed by treatment with simvastatin at a dose of 20µg/g body weight/day for 28days and they reported that simvastatin significantly inhibited fibroid tumor growth 10 Subsequently they carried out a nested case control study of >190,000 women to analyze the relation between use of statins at antihyperlipidemic doses and the risk of development of Uterine fibroid/ Uterine fibroid related symptoms.…”
mentioning
confidence: 99%
“…10 Use of statins correlated with lower odds ratio of developing uterine fibroid, menorhagia, anemia, pelvic pain or myomectomy in contrast to non users. 8 Subsequently Shen conducted a retrospective study in 120 patients having fibroid with hyperlipidemia where atorvastatin 20mg/day was…”
mentioning
confidence: 99%